The Role of Islam and Muslim Clergy in Economical Life of Central Asian Khanates - Gulchekhra Agzamova (Researchparks Publishing, 2021)
The author of the article joins the discussion on the assessment of the development of social-economical life of the Bukhara, Khiva and Kokand khanates at that era. Based on the analysis of the changes in internal life and international trade of the khanates. The article contains an analysis of the main changes made the development of social-economical life of Central Asian khanates and in its ruling according to Islam’s laws. Attention is drawn to the trends of weakening the repressiveness of clergymen’s participation in trade activity, as well as other representatives of clergy.